ANALISIS PERHITUNGAN DAN PELAPORAN PPH FINAL PASAL 4 AYAT 2 ATAS BUNGA DEPOSITO DAN TABUNGAN NASABAH PADA PT. BPR MAPALUS TUMETENDEN CABANG TOMOHON - Lolong, Veronica Junisa; Saerang, David Paul Elia; Wokas, Hence (GOING CONCERN : JURNAL RISET AKUNTANSI, 2016)
Income tax is one of the largest government revenues. Income Tax Law Article 4 Paragraph 2 gives a mandate to the government to impose income tax on certain earnings final. This study aims to determine how the interest calculation and interest reports and final income tax deduction on interest of savings and customer deposits at PT. BPR Mapalus Tumetenden Branch Tomohon. Descriptive analysis was employed in this study. Data were obtained by field studies. The results shows that the calculation and reports of Final Income Tax Article 4 Paragraph 2 on deposit and savings PT. BPR Mapalus Tumetenden Branch Tomohon have compiled with the laws of regulations. Leaders of PT. BPR Mapalus Tumetenden Branch Tomohon should improve the service quality to each customer, so that the customers can increase the amount of savings in bank. Keywords: calculation, reporting, deposit interest, customer savings